Silver nitrate and chlorhexidine gluconate – effective surface sterilization agents in disinfection procedures at initiation of woody shoot tip and embryo culture - Nacheva, Lilyana Rumenova; Ivanova, Valeria (Journal of BioScience and Biotechnology, 2018)
The surface sterilization of explants in chemical solutions is an important step to remove contaminants with minimal damage to plant cells. Woody and mature plants growing in the open field are known to harbor a large amount of microflora and are very difficult to sterilize. The routinely used surface sterilization procedures with solution of Ca(OCl)2 had proven to be relatively unsuccessful with Taxus baccata and some other woody fruit and ornamental species. The objective of the present study was to propose and to verify new procedures of surface-sterilization of Ginkgo and plum shoot tip explants from old trees as well as sweet cherry embryos employing silver nitrate or chlorhexidine gluconate in different concentration and periods of exposure. According to the results obtained in the present experiments we could recommend silver nitrate and chlorhexidine gluconate as effective surface sterilization agents in disinfection procedures at initiation of woody shoot tip and embryo culture.